STUDY OF COMPARISON ACHIEVEMENT BETWEEN MINUS GLASSES STUDENTS AND NOT IN CLASS XII SMA N 1 BOYOLALI - Yusak Dwi Prihantono; Kemaludin .; Akbar Amin Abdullah (STIKES DUTAGAMA KLATEN, 2017)
Background: Reading is the way to achieve good academic achievement. Many students take the time to read in order to obtain good results in academic achievement but not pay attention to health in reading can lead to eye disorders myopia, so they need for glass as tools for seeing. Unlike the case with students who rarely read, there is little possibility for irritated eyes myopia. Objective: To know differences abouth achievement between minus glasses student and not in class XII SMA N 1 Boyolali. Research Methods : non-experimental studies with ekspost facto research design with a population of 293 people and sampling techniques with Stratified Random Sampling obtained samples of 44 students and 44 students minus glasses without glasses. Results : independent samples t-test showed the t count (2.658) > t table (1.663) with probability 0.009 <0.05. Conclusion: There are differences in achievement between minus glasses students and not in the class XII SMA N 1 Boyolali.